Separation and purification of six components from the roots of Rheum officinale Baill. by supercritical fluid chromatography. Issue 3 (7th February 2017) - Qin, Xiuxiu; Wang, Yancui; Li, Aifeng; Sun, Ailing; Yu, Linlin; Liu, Renmin
ABSTRACT: The dried roots of Rheum officinale Baill., named Dahuang in Chinese, has many pharmacological effects and has been widely used for the treatment of many diseases. To develop a harmless and eco-friendly method for the separation of components in Dahuang is of great interest for quality control and pharmacological study of Dahuang. A method for separation and purification of components in Dahuang using supercritical fluid chromatography (SFC) is established in this work. Samples were prepared by extraction of Dahuang powders with 20% H2 SO4 and benzene under reflux. The extracts were obtained by evaporating benzene extracts and separating by SFC on YMC-Diol column using supercritical CO2 with CH3 OH 4% (v/v) as the modifier. The flow rate of the mobile phase was 15 mL/min, the column pressure was 13 MPa, and the column temperature was 318 K. Cinnamic acid and five kinds of hydroxyanthraquinones including rhein, emodin, aloe emodin, chrysophanol, and physcion were obtained by SFC. The purities of the obtained compounds were all above 97% as determined by high performance liquid chromatography and their chemical structures were identified by nuclear magnetic resonance and mass spectrum. The thermodynamics of chromatographic process was also studied and it revealed that the SFC separation process of these compounds on YMC-Diol column was controlled by enthalpy. GRAPHICAL ABSTRACT: